Climate-smart livestock systems: an assessment of carbon stocks and GHG emissions in Nicaragua - Gaitán, Lucía; Läderach, Peter R.D.; Graefe, Sophie; Rao, Idupulapati M.; Hoek, Rein van der (Public Library of Science, 2016)
Livestock systems in the tropics can contribute to mitigate climate change by reducing greenhouse gas (GHG) emissions and increasing carbon accumulation. We quantified C stocks and GHG emissions of 30 dual-purpose cattle farms in Nicaragua using farm inventories and lifecycle analysis. Trees in silvo-pastoral systems were the main C stock aboveground (16±24 Mg ha-1), compared with adjacent secondary forests (43 Mg C ha-1). We estimated that methane from enteric fermentation contributed 1.6 kg CO2-eq., and nitrous oxide from excreta 0.4 kg CO2-eq. per kg of milk produced. Seven farms that we classified as climate-smart agriculture (CSA) out of 16 farms had highest milk yields (6.2 kg cow-1day-1) and lowest emissions (1.7 kg CO2-eq. per kg milk produced). Livestock on these farms had higher-quality diets, especially during the dry season, and manure was managed better. Increasing the numbers of CSA farms and improving CSA technology will require better enabling policy and incentives such as payments for ecosystem services.